Leptophlebiidae (Ephemeroptera) from Roraima State, Brazil: description of two new species of Ulmeritoides Domínguez, 1991 - Neto, Jaime De Liege Gama; Bastos, Mahedy Araujo Passos (Zootaxa, 2016)
Two new species of Ulmeritoides Traver, 1959 from Northern Brazil are described based on male imagos. Ulmeritoides aurantifrons sp. nov. differs from all other species of the genus by the following combination of characters: mesonotum with a yellow spot in the apical and medial portions of the mesoscutal suture and a yellowish spot between the apex of the medioscutum and the posterior scutal protuberances, scutellum dark brown with base and apex yellow; forewing hyaline with two cross veins basal to bulla; penis lobes with a ventral groove, apically rounded. Ulmeritoides mirr sp. nov. differs from all other species of the genus by the following combination of characters: mesonotum with mesoscutal suture yellow; apex of the posterior scutal protuberance with a yellow transversal line; forewing hyaline, costal and subcostal areas tinged with light brown; penis lobes with a ventral groove, apically rounded.